Sugar Sweetened Beverage Consumption Among Adults With Children in the Home - White, Ashley H.; James, Shirley A.; Paulson, Sjonna W.; Beebe, Laura A. (Frontiers in Nutrition, 2018)
Introduction: Consumption of sugar sweetened beverages (SSB)s) has been linked with adult and childhood obesity, an increasing health burden in the United States. The aim of this study was to examine factors associated with the consumption of SSBs among Oklahoma adults with children in the home. Methods: A random sample of 1,118 Oklahoma adults with children in the home participated in a survey about their SSB consumption between August and October, 2015. by the Sooner Survey Center in the University of Oklahoma College of Public Health. We calculated weighted prevalence estimates and examined the relationship between types of SSBs consumed and covariates of interest using logistic regression techniques appropriate for survey data. Outcome variables included three categories of SSB consumption: consuming ≥1 sugar-sweetened sodas daily, consuming ≥1 other SSBs daily, and total daily SSB consumption, defined as ≥1 SSB of any kind. Heavy consumers were those who drank ≥3 SSBs per day. Results: Almost half (44%) of adults with children in the home consumed ≥1 total SSBs daily; 29% consumed ≥1 sugar-sweetened sodas and 28% consumed ≥1 other SSBs not including soda daily. The odds of consuming ≥1 SSBs daily was four times higher among those with a high school education or less (AOR = 4.06, 95% CI = 2.34, 7.04); almost three times higher for those who perceived their diet as somewhat healthy, or not very healthy (AOR = 2.72, 95% CI = 1.27, 5.82), more than double among those aged 18-34 years (AOR = 2.41, 95% CI = 1.08, 5.40), and almost double among those who consume <8 cups of water daily (AOR = 1.78, 95% CI = 1.06, 2.99). Conclusion: Because SSBs have been linked with obesity, understanding factors associated with consumption is important, especially among parents and caregivers of children. These findings have implications for developing and targeting messages to prevent SSB consumption among those most at risk.